Finite Element Analysis for Nonstationary Magneto-Heat Coupling Problem (Communications in Computational Physics, 2019)
This paper is devoted to finite element analysis for the magneto-heat coupling model which governs the electromagnetic fields in large power transformers.The model, which couples Maxwell's equations and Heat equation through Ohmicheat source, is nonlinear. First we derive an equivalent weak formulation for the nonlinear magneto-heat model. We propose a linearized and temporally discrete schemeto approximate the continuous problem. The well-posedness and error estimates areproven for the semi-discrete scheme. Based on the results, we propose a fully discretefinite element problem and prove the error estimates for the approximate solutions. Tovalidate the magneto-heat model and verify the efficiency of the finite element method,we compute an engineering benchmark problem of the International Compumag Society, P21b-MN. The numerical results agree well with experimental data.